Information Seeking Behaviors and Preferences of Cancer Survivors: A Cross-sectional Study in Shanghai, China - Mengying Liu; Yuan Xu; Jie Song; Xiaojing Hu; Chunlin Jin; Ziping Liu; Ruijia Li; Minxing Chen (Journal of Cancer Education, 2026)
The information needs of cancer survivors are numerous and chronically difficult to meet, and the information sources currently available to them are far from ideal. The purpose of this study was to investigate the information-seeking behaviors and preferences of cancer survivors and explore the differences in information needs among cancer survivors of different types in Shanghai, China. A quota sampling method was used to select cancer survivors living in all districts of Shanghai as the study population. Data collection used the Unmet Information Needs Scale for Cancer Patients. ANOVA were used to assess differences in unmet need scores among subgroups. The mean age of 4195 cancer survivors was 63.2 ± 7.4 years, comprising 823 males (19.6%) and 3372 females (80.4%). Among the current sources of information, 36.2% of cancer survivors opted for consultations with tertiary-level doctors. In terms of desired sources, 43.9% preferred tertiary-level doctors. Regardless of the current or future situation, tertiary-level doctors, patient friends, and primary care doctor remain the top three preferred sources for health information. Kidney cancer, metastatic cancer, and nasopharyngeal cancer demonstrated the highest information requirement scores, scoring 39.4, 37.5, and 36.6, respectively. Cancer survivors of different cancer types showed differences in focus and information needs. Current and expected information sources for cancer survivors differ at different stages of survival. Tertiary-level doctors are the most popular providers of information. Unmet information needs for different cancer types are diverse and complex.